The Effect of Gadget Use Duration on Informatics Students' Eye Health - Ottopianus Mellolo; Prayti Noviana Daleno; Desvita Christi Kilis; Valentino William Dumais; Stefanie Virginia Mongi; Syalom Karunia Kowimbin (Syntax Corporation Indonesia, 2024)
The technology that is developing in the current era can be seen in its progress. One of the technologies that is developing is the use of gadgets today. The use of gadgets today certainly helps users to communicate or find out existing information. However, the use of gadgets today is no longer used properly, especially the use of gadgets with excessive duration. This means that we often look at the gadget screen longer which can trigger bad things to happen in our lives. This writing aims to find out how students, especially informatics students, use gadgets in their daily lives. The use of gadgets by informatics students is certainly very necessary to help them in their daily lives on campus for their academics, help in making coding, etc. This research was conducted using a qualitative method, namely conducting observations through surveys distributed to students. From existing research, we see the results that informatics students on average use gadgets for more than 4 hours a day, even almost all day they use gadgets. Therefore, as students who often use gadgets, of course we must continue to pay attention to health or the impacts that will occur so that students are expected to maintain the duration of using gadget screens considering that it can have an impact on our eye health.